Sex hormone therapy in Multiple Sclerosis: A systematic review of randomized clinical trials - Monir Shayestehfar; Mehri Salari; Shahedeh Karimi; Massoud Vosough; Amirhossein Memari; Seyed Massood Nabavi (Journal of Central Nervous System Disease, 2024)
Background In spite of the observed immunomodulatory properties of different sex hormones on Multiple Sclerosis (MS) in different investigations, to date, there has been no study to systematically review the documents to add more powerful data to the field. Objectives Therefore, in this paper we aim to systematically review clinical and randomized controlled trials (RCT) assessing the effect of sex hormone therapies on individuals with MS. Design A comprehensive search of electronic databases including PubMed, EMBASE, and Scopus was conducted. Clinical trials and RCTs that assessed the impact of sex hormones on individuals with MS were selected and included in the systematic review. Data sources and methods In the final phase of the search strategy, 9 papers reached the criteria for entering in the systematic review. Two independent reviewers extracted the relevant data from each article according to the standardized data extraction form. Two reviewers also assessed the quality of each study independently using PEDro scale. Results We categorized three different classifications of outcomes including clinical, MRI, and immune system findings and put each measured outcome in the category which matched best. Conclusion In conclusion, the existed investigations on the effect of sex hormones on inflammatory and neurodegenerative components of MS are promising particularly in relapsing-remitting MS (RRMS).